2013
DOI: 10.1159/000352004
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Organization of the African Elephant Diencephalon and Brainstem

Abstract: The current study examined the organization of the diencephalon and brainstem of the African elephant (Loxodonta africana) - a region of the elephant brain that has not been examined for at least 50 years. The current description, employing material amenable for use with modern neuroanatomical methods, shows that, for the most part, the elephant diencephalon and brainstem are what could be considered typically mammalian, with subtle differences in proportions and topology. The variations from these previous de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 59 publications
(126 citation statements)
references
References 78 publications
4
118
4
Order By: Relevance
“…The highly sensitive tip of the trunk moves extensively as the elephant explores and manipulates its immediate environment. We speculate that the extraordinary number of neurons in the elephant cerebellum, and thus the large absolute and relative size of this structure (Maseko et al, 2012) as well as brainstem motor specializations (Maseko et al, 2013b), may have been driven by the processing of complex sensory and motor information regarding the trunk, a large sensorimotor unpaired appendage unique to the Proboscideans.…”
Section: Resultsmentioning
confidence: 98%
“…The highly sensitive tip of the trunk moves extensively as the elephant explores and manipulates its immediate environment. We speculate that the extraordinary number of neurons in the elephant cerebellum, and thus the large absolute and relative size of this structure (Maseko et al, 2012) as well as brainstem motor specializations (Maseko et al, 2013b), may have been driven by the processing of complex sensory and motor information regarding the trunk, a large sensorimotor unpaired appendage unique to the Proboscideans.…”
Section: Resultsmentioning
confidence: 98%
“…For example, the orexinergic cells within the hypothalamus can generally be divided into three magnocellular clusters, the main cluster, the zona incerta cluster and the optic tract cluster, although variations do exist (Kruger et al, 2010;Bhagwandin et al, 2011a,b;Gravett et al, 2011;Dell et al, 2012Dell et al, , 2013Calvey et al, 2013;Maseko et al, 2013;Patzke et al, 2014). One of the interesting variations found was the existence of a parvocellular medially located cluster of orexinergic neurons in the giraffe and harbour porpoise (Dell et al, 2012), which has since been reported in the African elephant (Maseko et al, 2013). Thus, the Cetartiodactyla as a group have an additional orexinergic nucleus normally not observed in other mammals.…”
Section: Evolutionarily Conservative Aspects Of the Orexinergic Systemmentioning
confidence: 99%
“…In most mammals the majority of these orexinergic neurons are found within the lateral hypothalamus and perifornical area, but have also been observed in the zona incerta region and the ventrolateral hypothalamus near the optic tract (Peyron et al, 1998;van den Pol, 1999;Wagner et al, 2000;Iqbal et al, 2001;Moore et al, 2001;Yoshida et al, 2006;Nixon and Smale, 2007;Datta and MacLean, 2007;Ettrup et al, 2010;Kruger et al, 2010;Bhagwandin et al, 2011a,b;Gravett et al, 2011;Calvey et al, 2013;Dell et al, 2013;Maseko et al, 2013). A study by Dell et al (2012) comparing the distribution and number of orexinergic neurons in the brain of the giraffe and harbour porpoise showed an additional novel medially located parvocellular cluster of orexinergic neurons in the hypothalamus of these two species, which has since also been reported in the African elephant (Maseko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies are beginning to demonstrate that the elephant brain, in overall appearance is, unsurprisingly, a typical, but large, mammalian brain; however, it does possess specializations associated with the auditory and vocalization systems [Cozzi et al, 2001;Maseko et al, 2013b], with the portion of the motor system related to the timing of movements [Maseko et al, 2012[Maseko et al, , 2013a, the presence of von Economo neurons [Hakeem et al, 2009], and a very large, both in relative and absolute terms, cerebellum [Maseko et al, 2012[Maseko et al, , 2013a. In addition, it is evident that the morphological complexity of some of the pyramidal neurons in the frontal cortex rivals those seen in human frontal cortex .…”
Section: The Trajectory Of Elephant Brain Evolutionmentioning
confidence: 99%